Straw collecting behaviour by pacas (Agouti paca) in captivity - Sabatini, V; da Costa, MJRP (Elsevier B.V., 2006)
Agouti paca is both considered as a species vulnerable to extinction and recognised with the potential for domestication. In spite of this, its behaviour is poorly documented and captive breeding is mainly based on trial and error. The aim of the present research was to analyse whether different strategies of straw supply could affect the behaviour and welfare of pacas in captivity. The study was done with eight adult pacas grouped in four mated pairs, three of them with one offspring. Each group was housed separately in 10 m 2 pens and the straw collecting behaviour was recorded. The quantity of straw collected per day was measured to compare four different strategies for straw supply and nest removal, where: every day nest removal treatment (1R) = supplying 1 kg of straw every day (outside the burrow) and removing all straw from inside the burrow every day; every 3 days nest removal treatment (3R) = supplying 1 kg every day and removing after 3, 6, and 9 days; no nest removal treatment (9R) = supplying 1 kg every day and removing after 9 days; nest deprivation treatment (Dep) = supplying 1 kg every day except at days 3, 4, and 5 and removing after 3 and 9 days. Straw collecting was always performed after 17:30 h, with three behavioural acts being performed: mouthing, transporting, and depositing the straw into the artificial burrow. The straw collected per day mean of 1R was significantly higher than the means of other treatments. During the deprivation period of Dep, chips cut from the eucalyptus branches and a great quantity of fruits and manioc were found inside the burrows. The motivation to collect seemed to increase as a consequence of straw deprivation. By these we conclude that straw should be offered to pacas in captivity, giving them the opportunity to collect straw by themselves. Doing this we expect to promote an effective environmental enrichment for this species in captivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: management; deprivation; environmental enrichment; animal welfare